Взаємозв’язки брехливості з диференційними типами рефлексії в корисливих злочинців-рецидивістів - Дроздова, Л. В.; Drozdova, L. V. (Габітус. - 2020. - Вип. 20. - С. 220-225, 2020)
Представлено теоретичний аналіз наукових праць у царині психології щодо особливостей рефлексії та прояву брехливості. Проаналізовано зміст феномена рефлексії й різних проявів брехливості. Рефлексія розглядається як здатність усвідомлювати й адекватно оцінювати себе та оточуючих. Брехливість аналізується як індивідуально-психологічна особливість корисливих злочинців-рецидивістів, які в кримінальній діяльності неодноразово вдавалися до брехні з метою отримання матеріальної винагороди й задоволення власних корисливих мотивів. Здійснено емпіричне дослідження взаємозв’язків брехливості з диференційними типами рефлексії в корисливих злочинців-рецидивістів.

The article presents a theoretical analysis of scientific works in the field of psychology on the features of reflection and the manifestation of deceit. The content of the phenomenon of reflection and various aspects of the manifestations of lying are analyzed. Reflection is seen as the ability to be aware of and adequately evaluate himself/herself and others. Lying is analyzed as an individual-psychological feature of asquisitive recidivist criminals, who in their criminal activity have repeatedly resorted to lying in order to obtain material reward and satisfy their own asquisitive motives. In accordance with the purpose and objectives of the work, an empirical study of the relationship between lying and differential types of reflection in asquisitive recidivists has been performed. The results of an empirical study of the phenomenon of lying and reflexive manifestations of personality in asquisitive recidivist criminals are revealed in detail. The sample consisted of 53 convicts who were imprisoned for crimes under the Criminal Code of Ukraine (fraud, extortion, robbery, theft).Two groups of subjects were formed, to which asquisitive criminals-recidivists were included on the basis of the results of cluster analysis on the principle of “nearest neighbour”. We used the questionnaire “Differential type of reflection” by D. Leontiev and “Structural and functional questionnaire of deceit” by I. Tserkovna. It is established that the first group of asquisitive criminals outperforms the second group of subjects in all differential types of reflection. It is determined that the differential types of reflection reveal differences in the structure of relationships with the structural and functional components of deceit in both groups, which indicates the specific contribution of reflection in the functioning of deceit in these respondents.

Представлен теоретический анализ научных трудов в области психологии относительно особенностей рефлексии и проявления лживости. Проанализировано содержание феномена рефлексии и различных проявлений лживости. Рефлексия рассматривается как способность осознавать и адекватно оценивать себя и окружающих. Лживость анализируется как индивидуально-психологическая особенность корыстных преступников-рецидивистов, которые в уголовной деятельности неоднократно прибегали ко лжи с целью получения материального вознаграждения и удовлетворения собственных корыстных мотивов. Осуществлено эмпирическое исследование взаимосвязей лживости с дифференциальными типами рефлексии у корыстных преступников-рецидивистов.
Interrelationships between lying and differential types of reflection in acquisitive criminals-recidivists
Дроздова, Л. В. Взаємозв’язки брехливості з диференційними типами рефлексії в корисливих злочинців-рецидивістів / Дроздова Л. В. // Габітус. - 2020. - Вип. 20. - С. 220-225. - DOI: https://doi.org/10.32843/2663- 5208.2020.20.40.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Юридична психологія. Legal psychology. Юридическая психология; рефлексія; reflection; рефлексия; брехливість; mendacity; лживость; особистість; personality; личность; корисливі злочинці; self-serving criminals; корыстные преступники; рецидивісти; recidivists; рецидивисты; диференційні типи рефлексії; differential types of reflection; дифференциальные типы рефлексии